2016
DOI: 10.1002/2016ja022741
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of small size magnetic holes in the magnetospheric plasma sheet

Abstract: Magnetic holes (MHs), characteristic structures where the magnetic field magnitude decreases significantly, have been frequently observed in space plasmas. Particularly, small size magnetic holes (SSMHs) which the scale is less than or close to the proton gyroradius are recently detected in the magnetospheric plasma sheet. In this study of Cluster observations, by the timing method, the minimum directional difference (MDD) method, and the spatiotemporal difference (STD) method, we obtain the propagation veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…Those KSMHs contain electron vortices similar to the MP and their scale size is tens or several tens of ρ e , close to the MP scale. Actually, the KSMHs are observed not only in the magnetosheath but also in the plasma sheet (Ge et al, ; Gershman et al, ; Sun et al, ; Sundberg et al, ; Yao et al, ; Zhang et al, ). The KSMHs in the plasma sheet are also of similar scale size to the MP.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those KSMHs contain electron vortices similar to the MP and their scale size is tens or several tens of ρ e , close to the MP scale. Actually, the KSMHs are observed not only in the magnetosheath but also in the plasma sheet (Ge et al, ; Gershman et al, ; Sun et al, ; Sundberg et al, ; Yao et al, ; Zhang et al, ). The KSMHs in the plasma sheet are also of similar scale size to the MP.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The KSMHs in the plasma sheet are also of similar scale size to the MP. Furthermore, these observations display a depolarized magnetic field (Ge et al, ), an electron vortex (Gershman et al, ; Zhang et al, ), and propagation with respect to the plasma flow (Yao et al, ), analogous to the properties of the MP. Thus, we speculate that the MP and the KSMHs could be intrinsically linked.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Kinetic-scale magnetic dips (KSMDs) are a significant depression of magnetic field strength with a scale size close to or less than a proton gyroradius (ρ i ). These structures have been observed both in the Earth's magnetospheric plasma sheet (e.g., Ge et al, 2011;Gershman et al, 2016;Goodrich et al, 2016;Sun et al, 2012;Sundberg et al, 2015;Yao et al, 2016;Zhima et al, 2015;Zhang et al, 2017) and magnetosheath (e.g., Yao et al, 2017). In addition to observational investigations, KSMDs have also been extensively studied through theoretical analysis and numerical simulations (e.g., Balikhin et al, 2012;Haynes et al, 2015;Ji et al, 2014;Li et al, 2016;Roytershteyn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the mirror-mode structures are generated in high plasma beta (the ratio of the plasma pressure to the magnetic pressure) regions, with the perpendicular plasma pressure being greater than parallel plasma pressure. They were also often considered a possible source of magnetic dips in many studies (e.g., Ahmadi et al, 2017;Horbury et al, 2004;Joy et al, 2006;Shi et al, 2009;Xiao et al, 2014;Zhang et al, 2008), though different mechanisms were proposed by others (e.g., Balikhin et al, 2012;Ji et al, 2014;Li et al, 2016;Yao et al, 2016Yao et al, , 2017Yao et al, , 2018. Furthermore, their spatiotemporal scales and evolution processes, three-dimensional (3-D) structures, and other important kinetic effects (e.g., drift, finite Larmor radius effect, non-Maxwellian ion distribution, and electron temperature influence) were also extensively investigated (e.g., Ahmadi et al, 2016;Chisham et al, 1998;Feygin et al, 2009;Gary & Karimabadi, 2006;Gedalin et al, 2001;Genot et al, 2009;Hasegawa, 1969;Hellinger et al, 2009;Klimushkin & Chen, 2006;Pokhotelov et al, 2013;Pokhotelov & Pilipenko, 1976;Treumann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%